2012
DOI: 10.7845/kjm.2012.48.2.125
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Diversity in Three-Stage Methane Production Process Using Food Waste

Abstract: Anaerobic digestion is an alternative method to digest food wastes and to produce methane that can be used as a renewable energy source. We investigated bacterial and archaeal community structures in a three-stage methane production process using food wastes with concomitant wastewater treatment. The three-stage methane process is composed of semianaerobic hydrolysis/acidogenic, anaerobic acidogenic, and strictly anaerobic methane production steps in which food wastes are converted methane and carbon dioxide. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Biogas produced by acetogenesis in the anaerobic digestion process with swine manure was 72%, and biogas produced by hydrogenotrophic methanogen was 28% (Lee et al, 2005). However, biogas produced by acetogenesis in the anaerobic digestion process with a mixture of food waste and swine manure was 4%, and biogas produced by hydrogenotrophic methanogen was 96% (Nam et al, 2012). Kafle and Kim et al (2013) reported similar results: they processed a mixture of swine manure and silage that was made with saury and rice bran to supplement protein and fat and obtained 801 mL/g VS of biogas, which was 6% higher than when only swine manure was used (711 mL/g VS).…”
Section: Mixture Of Food Waste and Swine Manurementioning
confidence: 95%
See 1 more Smart Citation
“…Biogas produced by acetogenesis in the anaerobic digestion process with swine manure was 72%, and biogas produced by hydrogenotrophic methanogen was 28% (Lee et al, 2005). However, biogas produced by acetogenesis in the anaerobic digestion process with a mixture of food waste and swine manure was 4%, and biogas produced by hydrogenotrophic methanogen was 96% (Nam et al, 2012). Kafle and Kim et al (2013) reported similar results: they processed a mixture of swine manure and silage that was made with saury and rice bran to supplement protein and fat and obtained 801 mL/g VS of biogas, which was 6% higher than when only swine manure was used (711 mL/g VS).…”
Section: Mixture Of Food Waste and Swine Manurementioning
confidence: 95%
“…Nam et al (2012) investigated microbial community changes of bacteria and archaea in the anaerobic digestion process when using a mixture of food waste and livestock wastewater. They presented a three-step methane production process of livestock wastewater based on acetogenesis, but the process of using food waste was based on hydrogenotrophic methanogen.…”
Section: Mixture Of Food Waste and Swine Manurementioning
confidence: 99%